Incidencia de las técnicas grafo plásticas para desarrollar la motricidad fina en el proceso de enseñanza-aprendizaje en los niños y niñas del primer año de la Escuela de Educación Básica Presidente Jaime Roldós Aguilera pertenecientemente a la parroquia 9 de Mayo, de la ciudad de Machala, período lectivo 2012-2013. - Jaramillo Chuquirima, Valeria Alexandra (2013)
Assuming that the hypothetical approach was affirmative, a Manual of Plastic Techniques has been developed to develop the fine motor skills in children of the first year of Basic Education, to generate a favorable and beneficial application for both teacher, student and parent , And to achieve in a great sense the psychomotor and affective development in the infants.